2015
DOI: 10.1002/adfm.201502079
|View full text |Cite
|
Sign up to set email alerts
|

m‐Indolocarbazole Derivative as a Universal Host Material for RGB and White Phosphorescent OLEDs

Abstract: The host materials designed for highly efficient white phosphorescent organic light‐emitting diodes (PhOLEDs) with power efficiency (PE) >50 lm W‐1 and low efficiency roll‐off are very rare. In this work, three new indolocarbazole‐based materials (ICDP, 4ICPPy, and 4ICDPy) are presented composed of 6,7‐dimethylindolo[3,2‐a]carbazole and phenyl or 4‐pyridyl group for hosting blue, green, and red phosphors. Among this three host materials, 4ICDPy‐based devices reveal the best electroluminescent performance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 68 publications
2
67
0
Order By: Relevance
“…However, we will see that this angle can be modulated depending of the nature of the substituent borne by the fluorene (see part 5). In order to obtain high-efficiency PhOLEDs, a good charge balance is necessary in the host and many different building blocks have been used for this purpose such as indolocarbazole, 85 phenylacridine, 60,61,86 indoloacridine, 63 phosphine oxide, 40,53,56 pyridine, benzimidazole 68 among others. However, it has been shown that the C-C bond is significantly stronger than the C-S, C-P or C-N bonds.…”
Section: -Ph-sbfmentioning
confidence: 99%
“…However, we will see that this angle can be modulated depending of the nature of the substituent borne by the fluorene (see part 5). In order to obtain high-efficiency PhOLEDs, a good charge balance is necessary in the host and many different building blocks have been used for this purpose such as indolocarbazole, 85 phenylacridine, 60,61,86 indoloacridine, 63 phosphine oxide, 40,53,56 pyridine, benzimidazole 68 among others. However, it has been shown that the C-C bond is significantly stronger than the C-S, C-P or C-N bonds.…”
Section: -Ph-sbfmentioning
confidence: 99%
“…Remarkably, the device is highly efficient at large current densities. The energy conversion efficiency (wall-plug efficiency) of our NFPI6B MQW LED is 5.5% at 100 mA cm -2 , which is more efficient than the state-of-the-art vacuum-deposited organic LEDs at this high current density (Supplementary Table S2) [24][25][26] . The EQE histogram for 70 NFPI6B-MQW LEDs shows an average peak EQE of 8.8% and a small relative standard deviation of 11% (Fig.…”
mentioning
confidence: 93%
“…In this case, independent display pixels responsible for different color outputs can be fabricated with an analogous or even identical configuration, and single or multiple EMLs of lighting diodes can also be assembled expediently. However, to date, very few high-performance universal host materials for monochrome and white OLEDs are available in the literature 1719. The scarcity of efficient universal hosts should be ascribed to the diverse requirements of multiple phosphorescent dopants, such as different frontier orbital levels, molecular polarities and host–guest interactions.…”
Section: Introductionmentioning
confidence: 99%